Anti-endothelial cell antibodies in insulin-dependent diabetes mellitus. - Wangel, A G (1992)
The prevalence of IgG class antibodies to endothelial cells (AECA) was studied in 136 young patients with insulin-dependent diabetes mellitus by an enzyme immunoassay using human umbilical cord vein endothelial cells. The patients were divided into four groups according to the time between diagnosis and study and their results were compared with those in control children and blood donors. AECA became progressively more frequent with the duration of diabetes, being 4% in diabetics tested within 2 weeks of diagnosis and reaching 34% after an average disease duration of 11.2 years. They were not more common in patients with neuropathy, retinopathy or nephropathy than in patients without these complications, but were associated with co-existing thyroid disease and IgA deficiency. The results suggest that in insulin-dependent diabetes mellitus AECA are associated with co-existing autoimmune disorders but not with diabetic microvascular disease.